7x + 6 = 8x
6 = x
2007-09-09 21:44:02
·
answer #1
·
answered by Como 7
·
0⤊
0⤋
If you are solving for x:
1) 7x = 8x - 6
2) Subtract 8x from both sides of the equation so it beomes: 7x - 8x = 8x - 8x -6
3) That becomes: -1x = -6
4) Divide both sides by -1: -1x divided by -1 = -6 divided by -1
5) It becomes: x = 6.
Now, to make sure your answer is correct, plug it in the orginal equation:
7x = 8x - 6
7 (6) = 8 (6) - 6
42 = 48 - 6
42 = 42
It works and therefore, x = 6 is correct.
2007-09-06 19:35:52
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
move the 6 over to the 7x side and make it positive:
7x + 6 = 8x
then subtract 7x from both sides:
6 = 1x
x = 6
2007-09-06 19:32:01
·
answer #3
·
answered by David L 3
·
0⤊
0⤋
get the x's on one side of the = mark:
7x=8x-6
-8x -8x
-1x=-6
/-1 /-1
x=6
2007-09-06 19:33:24
·
answer #4
·
answered by JWilridge 3
·
0⤊
0⤋
7x=8x-6
add 6 to each side
6+7x=8x
minus 7x from each side
x=6
2007-09-06 19:31:44
·
answer #5
·
answered by becca f 1
·
0⤊
0⤋
7x=8x-6
subtract 8x from both sides
-1x=-6
x=6
Check:
7(6)=8(6)-6
42=48-6
42=42
2007-09-06 19:33:24
·
answer #6
·
answered by Schmoopy 2
·
1⤊
0⤋
add 6 to each side
7x+6=8x
subtract 7x from each side
6=x
2007-09-06 19:31:53
·
answer #7
·
answered by ECJacket 2
·
0⤊
0⤋
7x=8x-6
-1x=-6
x=6
2007-09-06 19:35:38
·
answer #8
·
answered by VTSOXFAN 4
·
0⤊
0⤋
7x=8x-6
6=8x-7x
6=x
2007-09-06 19:32:24
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋
subtract 8x from both sides so it will look like this:
-x = -6
then make each one positive...
x = 6
:)
2007-09-06 19:32:41
·
answer #10
·
answered by Kati S 2
·
0⤊
0⤋